Rancang Bangun Pendeteksi Kadar Formalin pada Mie Basah Menggunakan Sensor Warna TCS3200 : Design and Development of Formalin Contents Detection in Wet Noodles using Color Sensor TCS3200 - Rani Laras Wati; Endang Rosdiana; Valentina Adimurti Kusumaningtyas (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Wet noodles have a short shelf life because they are spoiled more quickly by microorganisms. Therefore, some irresponsible wet noodle producers add formalin so that the noodles can last longer. However, formalin is a substance that is prohibited from being used because it is dangerous to health. In this research, an instrument has been made that can detect formalin levels in wet noodles which have formalin concentrations of 0 ppm, 40 ppm, 95 ppm and 150 ppm. The instrument consists of a TCS3200 color sensor and an ATmega328P microcontroller. The color detected by the TCS3200 sensor is the color from mixing the formalin wet noodle sample withreagent schiff's. Furthermore, the sample will be selected by the instrument based on the RGB color value detected by the TCS3200 color sensor. The test results obtained the reliability of the instrument in selecting the sample of formalin wet noodles with a concentration of 0 ppm worth 92.5%, 40 ppm worth 95%, 95 ppm worth 97.5% and 150 ppm worth 100%.